Strengths and Weaknesses of Selected Modeling Methods Used in Systems Biology - Kahlem, Pascal; DiCara, Alessandro; Durot, Maxime; Hancock, John M.; Klipp, Edda; Schächter, Vincent; Segal, Eran; Xenarios, Ioannis; Birney, Ewan; Mendoza, Luis (IntechOpen, 2011)
None